Gouverner la télémédecine. Analyse institutionnaliste d’une nouvelle pratique médicale - Amandine Rauly (Revue de la Régulation)
This thesis questions the governance of telemedicine. In France Telemedicine is not developing as the public authorities have desired. The general hypothesis of our research is that instead of removing barriers to the development of telemedicine, public policies dedicated to its practice are actually impeding it. That is why we analyze power relations among stakeholders of regulation. To do this we adopt an institutionalist approach. We question the relevance of the governance model used for for deployment of telemedicine. We highlight that the solutions provided by the institutions in charge of the development of telemedicine can be improductive.